(untitled) (Latakia University Journal -Basic Sciences Series, 2021)
In this paper, two new concepts are presented the first is - accumulation point of filter and the second -closure point of filter. After that, -compact spaces are investigated corresponding to this two concepts. Moreover, the concept of -normal space is defined and relationships between it and the -regular space and the -compact space.